2018
DOI: 10.1038/s41588-018-0204-y
|View full text |Cite
|
Sign up to set email alerts
|

Mutational processes shape the landscape of TP53 mutations in human cancer

Abstract: Unlike most tumor suppressor genes, the most common genetic alterations in tumor protein p53 (TP53) are missense mutations. Mutant p53 protein is often abundantly expressed in cancers and specific allelic variants exhibit dominant-negative or gain-of-function activities in experimental models. To gain a systematic view of p53 function, we interrogated loss-of-function screens conducted in hundreds of human cancer cell lines and performed TP53 saturation mutagenesis screens in an isogenic pair of TP53 wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
420
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 393 publications
(481 citation statements)
references
References 52 publications
28
420
1
1
Order By: Relevance
“…Outcomes were reported as the relative enrichment (Z score) of individual variants under the selective conditions, which again allowed comparison to the output of the model. In a conservative approach to infer LOF, the cut‐off selected was −0.21 for etoposide assays, which showed the best separation between silent and common cancer missense variants as reported in the published data (Figure f in Giacomelli et al, ).…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…Outcomes were reported as the relative enrichment (Z score) of individual variants under the selective conditions, which again allowed comparison to the output of the model. In a conservative approach to infer LOF, the cut‐off selected was −0.21 for etoposide assays, which showed the best separation between silent and common cancer missense variants as reported in the published data (Figure f in Giacomelli et al, ).…”
Section: Methodsmentioning
confidence: 88%
“…Variants classified as pathogenic or likely pathogenic by the model were associated with earlier age of cancer onset (including a greater proportion of pediatric cancers), and were enriched in Classic LFS probands and depleted in a cohort of cancer-free women over 70 years. When compared to the output of reported functional assays, the majority of variants classified as pathogenic or likely pathogenic were nonfunctional in transactivation yeast assays (Kato et al, 2003), showed disruption of antiproliferative function/LOF (Giacomelli et al, 2018;Kotler et al, 2018), or reduced activity in the mammalian clonogenic survival assays developed in this study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…TP53 is one of the most well‐studied tumor‐suppressor genes. However, TP53 mutations or deletions are present in nearly 50% of human cancers and primarily result in impaired tumor‐suppressor function . Our bioinformatic studies showed that PSLNR was significantly involved in the regulation of cell proliferation, apoptosis, and the p53 signaling pathway.…”
Section: Discussionmentioning
confidence: 80%